Місце історичного матеріалу в процесі навчання математики - Месарош Лівіа; Livia Mesarosh; Mészáros Lívia (Ужгородський національний університет, 2024)
Резюме. Актуальність дослідження полягає необхідності підвищення рівня знань учнів з математики. Одним із засобів ефективного навчання є системне використання історичного матеріалу. Мета статті: висвітлення проблем у процесі навчання математики у контексті питання покращення ефективності навчального процесу через введення елементів історії. Методи дослідження: синтез і систематизація наукової літератури; аналіз динаміки історії математики у навчальному процесі; узагальнення; педагогічний досвід. Розглянуто можливості включення історико-математичних знань до навчального процесу у школі. Наведено математичні задачі із використанням історичних фактів, через які відображаються міжпредметні зв`язки. Існують перешкоди, з якими стикаються вчителі при впровадженні історичного матеріалу у свою роботу, такі як відсутність єдиного методичного підходу, обмеження в часі, потреба додаткової підготовки.

Abstract. The relevance of the research under consideration lies in the need to level up the knowledge of students on mathematics. One of the means of effective teaching is the systematic use of historical material. The purpose of the article is to highlight a set of issuesin the process of teaching mathematics in the context of improving the effectiveness of the educational process through the introduction of elements of history, designed to make learning more thorough, effective, and interesting. Research methods applied in the article: synthesis and systematization of scientific literature from educational and methodological publications, information resources of the Internet ‒ to clarify, compare, and contrast approaches in the direction of the outlined problem; analysis of the dynamics of the history of mathematics in the educational process, its importance for the formation of mathematical knowledge of the younger generation, generalization of the publications of scientists, pedagogical experience. The possibilities of including historical and mathematical knowledge in the educational process at school are considered. Examples of mathematical problems with the use of historical facts are provided, through which intersubject connections are reflected. It is established that there are obstacles faced by teachers when introducing historical material into their work, such as the lack of a single methodical approach, time constraints, and the need for additional training. Based on the data obtained, conclusions are made on the significance of using historical material in mathematics lessons, its positive impact on the motivation of students, and the activation of the educational process.
The place of historical material in the process of teaching mathematics
Keywords: математичні задачі; iсторичний матеріал; mathematical problems; historical material